Adhesive wear behavior and microstructure of FeCr-FeMn-FeB-C coatings - Yaz, Mehmet (Walter de Gruyter Gmbh, 2024)
This study employs a high-energy-density gas tungsten arc welding (GTAW) process to fabricate a surface coating on a substrate of 0.15 percent carbon steel, incorporating powders of FeCr, FeMn, FeB, and graphite. The investigation encompasses a multifaceted approach, utilizing X-ray diffraction (XRD), optical micrograph (OM) analysis, energy-dispersive X-ray analysis (EDS), scanning electron microscopy (SEM) imaging, microhardness testing, and adhesive wear testing, with the aim of examining the composite coating's microstructural attributes, microhardness, and performance under dry-sliding wear conditions. The research findings reveal the formation of diverse carbides and borides, including Mn5C2, Fe3C, B8C, B4C, Fe3B, Fe7C3, FeB, and MnB on the coated surfaces. Notably, the graphite particles within the FeB-FeMn-FeCr-C composite TIG welding coatings exhibit a range of morphologies, varying from sheet-like to dendritic structures.
Keywords: FeCr; FeB; FeMn; adhesive wear; coating